Patient Preferences and Knowledge Regarding Hysterectomy: A Study from the Fellows' Pelvic Research Network (FPRN)®. Issue 7 (8th July 2021) - Jacobs, Kristin M.; Hokenstad, Erik D.; Park, Beau Y.; Hamner, Jennifer J.; Shannon, Megan B.; Zigman, Jessica S.; Pilkinton, Marjorie L.; Mahal, Amandeep S.; Sheyn, David D.; Elmer-Lyon, Caroline G.; Korbly, Nicole B.; Sung, Vivian W.
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The purpose of this study was to describe preference for and knowledge of hysterectomy routes in women presenting to urogynecology/gynecology clinics throughout the United States and to determine association with health literacy. Our primary aim was preference for hysterectomy route, and secondary aims were knowledge of basic pelvic structures and function, knowledge of various hysterectomy routes, and baseline health literacy level. Methods: This multicenter, cross-sectional study was conducted through the Fellows' Pelvic Research Network. Patients' preference and knowledge for hysterectomy routes were assessed at initial presentation to the urogynecology/gynecology clinic with an anonymous, voluntary, self-administered questionnaire along with a validated health literacy test (Medical Term Recognition Test). Results: Two hundred four women participated. Forty-five percent of patients were unsure which hysterectomy modality they would choose. Of patients who selected a preferred modality, 50% selected laparoscopic and 33% selected vaginal. Patients indicated that safety was considered highest priority when selecting route. The mean score for "knowledge about gynecology/hysterectomy" was 68%, with the high literacy group scoring higher compared with the low health literacy group (70% vs 60.1%, P = 0.01). More than 50% of patients incorrectly answered knowledge questions related to vaginal hysterectomy. Majority of the respondents had high health literacy (79.4%). Conclusions: Patients prefer laparoscopic hysterectomy approach, although have limited understanding of vaginal hysterectomy. Higher health literacy levels are associated with increased knowledge of gynecology and hysterectomy routes, but were not found to influence patient preference for hysterectomy route. Overall, patients have limited knowledge of vaginal hysterectomy.